Neurogenetics and Epigenetics in Impulsive Behaviour: Impact on Reward Circuitry - Archer, Trevor (2012)
Adverse, unfavourable life conditions, particularly during early life stages and infancy, can lead to epigenetic regulation of genes involved in stress-response, behavioral disinhibition, and cognitive-emotional systems. Over time, the ultimate final outcome can be expressed through behaviors bedeviled by problems with impulse control, such as eating disorders, alcoholism, and indiscriminate social behavior. While many reward gene polymorphisms are involved in impulsive behaviors, a polymorphism by itself may not translate to the development of a particular behavioral disorder unless it is impacted by epigenetic effects. Brain-derived neurotrophic factor (BDNF) affects the development and integrity of the noradrenergic, dopaminergic, serotonergic, glutamatergic, and cholinergic neurotransmitter systems, and plasma levels of the neurotrophin are associated with both cognitive and aggressive impulsiveness. Epigenetic mechanisms associated with a multitude of environmental factors, including premature birth, low birth weight, prenatal tobacco exposure, non-intact family, young maternal age at birth of the target child, paternal history of antisocial behavior, and maternal depression, alter the developmental trajectories for several neuropsychiatric disorders. These mechanisms affect brain development and integrity at several levels that determine structure and function in resolving the final behavioral expressions.